2019
DOI: 10.3390/app9163300
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Text Corpus-Based Tourism Big Data Mining

Abstract: With the massive growth of the Internet, text data has become one of the main formats of tourism big data. As an effective expression means of tourists' opinions, text mining of such data has big potential to inspire innovations for tourism practitioners. In the past decade, a variety of text mining techniques have been proposed and applied to tourism analysis to develop tourism value analysis models, build tourism recommendation systems, create tourist profiles, and make policies for supervising tourism marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 134 publications
(153 reference statements)
0
74
0
1
Order By: Relevance
“…Text mining works with a wide range of disciplines, such as statistics, artificial intelligence and natural language processing, to analyze data from natural language texts (Miner et al, 2012). Text mining uses the methods of text classification, text clustering, topic extraction, sentiment analysis or opinion mining by using the disciplines mentioned above (Li et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Text mining works with a wide range of disciplines, such as statistics, artificial intelligence and natural language processing, to analyze data from natural language texts (Miner et al, 2012). Text mining uses the methods of text classification, text clustering, topic extraction, sentiment analysis or opinion mining by using the disciplines mentioned above (Li et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Text analysis is a sort of natural language processing (NLP) technology. NLP has gone through an array of technologies such as naive Bayes, TF/IDF, word2vec, LDA, LSTM, fast- text, BERT and even the latest ALBERT [21,22], which has vastly improved the text analysis quality and efficiency. The analysis process of recent researches on visitors' behaviours can be classified into two categories.…”
Section: Text Analysis and Latent Dimension Identificationmentioning
confidence: 99%
“…After an interview with the user, in their opinion, the advantage of this system is to find the link and idea for each tourist attraction, and to provide the users with new tourists. (5) According to the research by Li et al (2019) [30], text corpus-based tourism helps to observe and realize changes in the tourism market. OTR in this study is viewed as a kind of text corpus based tourism, which of the direction is confirmed to be correct, because the study by Gong, et al (2018) [31] has the same opinion.…”
Section: Conclusion and Further Workmentioning
confidence: 99%